Conservation, Production and Marketing of Red Sanders, Pterocarpus santalinus L.f. - Sarangi, Prafulla Kumar (Indian Forester, 2010)
During the last 4 to 5 years, large scale seizures of Red Sanders Wood are reported mostly from sea ports and border areas of our country with the help of customs and army authorities, though RS wood is mostly found in the state of Andhra Pradesh. The forest departments of other states are frequently reminding the State Government of AP to send expert officers from AP to their states to suggest grading, classification and the sale and export procedure. The procedure of sale of RS wood and its export to other countries are not known to the forest departments of other states. To have a detailed picture of conservation, production, classification, sale procedure and export policy of Government of India on Red Sanders are described in this article to have a first hand knowledge of the RS business and its export to other countries.